The Influence of Financial Performance, Operational Efficiency, and Corporate Social Responsibility on Firm Value: Evidence from Banking Companies Listed on the Indonesia Stock Exchange During 2022–2024 - Abdul Ghofur; Muhammad Choirul (PT. Mawadaku Sukses Solusindo, 2026)
This study aims to analyze the influence of Return on Assets (ROA), Return on Equity (ROE), Operating Expenses to Operating Income Ratio (BOPO), and Corporate Social Responsibility (CSR) on firm value in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The banking sector was selected because of its strategic role in the Indonesian economy and its dependence on public trust and financial stability. Amid increasing economic uncertainty and competitive market dynamics, maintaining firm value has become an important objective for banking institutions in order to sustain investor confidence and long-term business continuity. This research employed a quantitative approach using secondary data obtained from annual reports, financial statements, and sustainability reports published by banking companies listed on the IDX. The population consisted of 47 banking companies, while the final sample included 21 companies selected through purposive sampling techniques based on predetermined criteria. The total observation data amounted to 63 observations over a three-year period. Data analysis was conducted using SPSS through descriptive statistical analysis, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results demonstrate that Return on Assets (ROA) significantly influences firm value, indicating that profitability generated from company assets affects investor perceptions regarding corporate performance and growth prospects. Return on Equity (ROE) also has a significant effect on firm value, suggesting that the company’s ability to generate returns from shareholder equity contributes positively to market valuation. In contrast, BOPO does not significantly influence firm value, implying that operational efficiency is not the primary consideration for investors in evaluating banking companies. Meanwhile, Corporate Social Responsibility (CSR) significantly affects firm value, indicating that non-financial factors and sustainability-related disclosures increasingly influence investor assessments and corporate reputation. The findings of this study support agency theory, which emphasizes the importance of managerial performance and transparency in reducing agency conflicts and strengthening investor trust. This study contributes to the literature on corporate finance and banking management by providing empirical evidence regarding the determinants of firm value in the Indonesian banking sector during the post-pandemic economic recovery period.